Preparation and characterization of short kenaf fiber-based biocomposites reinforced with multi-walled carbon nanotubes. (1st April 2019) - Yaghoobi, Hessameddin; Fereidoon, Abdolhossein
Abstract: This paper presents the experimental study on the mechanical and thermal properties of nano-biocomposite made of polypropylene/kenaf fiber/polypropylene-grafted maleic anhydride (PP/kenaf/PP-g-MA) biocomposite and multiwall carbon nanotubes (MWCNTs). To meet this objective, the specimens were produced with different contents of MWCNTs (0, 0.5, 1, 1.5 and 2 wt%) by melt blending process in an internal mixer and in the following the standard form of specimens were made by compression molding. The amounts of chopped kenaf fiber loading and PP-g-MA compatibilizer were fixed at 30 wt% and 5 wt% for all formulations based on the preliminary studies. Tensile strength and modulus, flexural strength and modulus and notched Izod impact strength of the nano-biocomposites were evaluated, which obviously found that the mechanical properties of PP/kenaf/PP-g-MA biocomposites were enhanced by the addition of MWCNTs. The optimum in mechanical strengths was detected at 1 wt% MWCNTs. Thermogravimetric analysis (TGA) was carried out to investigate the thermal stability of nano-biocomposites. The results illustrated that the values of the different weight loss temperatures and second decomposition peak temperatures increased after incorporation of MWCNTs due to barrier effect of the MWCNTs. Morphological study which characterized using scanning electron microscopy (SEM) technique verified that a good and homogeneous distribution of MWCNTs through the biocomposites. However, some aggregates were revealed at higher MWCNT content. Fourier transform infrared (FTIR) spectroscopy analysis did not show any chemical interaction between MWCNTs and the PP/kenaf/PP-g-MA biocomposites.